Performance analysis of incremental hybrid decode-amplify-forward cooperative relaying with relay selection in Nakagami-m fading channels. (November 2018) - Shukla, Ashish Kant; Yadav, Suneel
Abstract: In this paper, we investigate the performance of incremental hybrid decode-amplify-forward relaying (IHDAF) protocol for the dual-hop cooperative multi-relay networks. We deduce a tight closed-form expression for the outage probability (OP) by employing opportunistic relay selection (ORS) under Nakagami- m fading channels. We further derive an asymptotic outage expression in the high signal-to-noise ratio (SNR) regime, from which the diversity order is examined. Based on the asymptotic results, we also present an optimal relay location to minimize the overall system outage. In addition, we derive new tight closed-form expressions of ergodic capacity and asymptotic ergodic capacity for the considered system. Finally, numerical and simulation results show the correctness of our analytical findings and the performance enhancement of the considered system with ORS-IHDAF scheme compared with the other incremental ORS-based cooperative schemes.